Implementatton of QR Code On Employee Attendance Applications Using Bootstrap - Khairina, Nadia Luthfiah; Irawan, Muhammad Dedi (Journal of Computer Science and Informatics Engineering, 2022)
The development of information technology is needed today and plays an important role in almost every aspect of human life. This is marked by the increasing use of computers and the internet in various fields. One of them is the work area, which can speed up work and of course manage data and find the information needed more accurately. PT Perkebunan Nusantara II or commonly abbreviated as PTPN II is a subsidiary of PTPN III which is engaged in plantation agribusiness. This study aims to assist companies in completing the attendance system that still uses the manual method. The application developed will use mySQL, PHP, Codeigniter with Visio which is used to design the application design that will be created and then designed based on the waterfall method. Problems that will occur in the future, such as an employee forgetting to sign the absentee but he has returned home as a result, the next day he also signed in the absent column last night by designing a QR Code-based attendance system to make it easier for employees to carry out attendance and make it easier for the Personnel to recap attendance . The application successfully runs according to the method applied with the following stages: requirements analysis, system design, program code writing, program testing and program implementation and maintenance.